Efeito anti-inflamatório do GDNF: qual a sua contribuição para a neuroprotecção dopaminérgica? - Roxo, Tiago Filipe Dias Santos (2013)
Microglia are the resident macrophages of the Central Nervous System and act as the main form of immune defence. Microglia can assume an activated state in case of inflammation, having its phagocytic activity increased, also releasing reactive oxygen species, in order to protect the Central Nervous System cells from injury. However, activated microglia has also been associated with neurodegeneration. Increased interleukin and cytokine levels have been described in neurodegenerative diseases, namely Parkinson’s disease, where the loss of dopaminergic neurons has been related to excessive microglial activation. Soluble factors released by astrocytes are capable to modulate microglial reactivity. From these factors, glial cell line-derived neurotrophic factor (GDNF) stood out for its ability to protect dopaminergic neurons from injury, both in vitro an in vivo. Some studies have also demonstrated an anti-inflammatory action of GDNF, mediated by its receptor GFR1, suggesting that these two effects of GDNF may be related to each other. However, no study has provided a clear evidence for a cause-effect relationship between them. Therefore, this work aims at elucidating the importance of GDNF control of microglial reactivity to the survival of dopaminergic neurons. The main strategy will be to block the action of GDNF specifically in microglial cells, through GFR1 silencing, and to evaluate its effect on the neuroprotective action of GDNF in the presence of an inflammatory stimuli. The expression of GFR1 in primary ventral midbrain microglia and N9 microglia cell line cultures was confirmed through immunochemistry and Western Blot. Silencing of GFR1, through siRNA, in N9 microglia cells was successfully accomplished and preliminary results suggest that silencing of this receptor in primary cultures of microglia is also doable. Co-cultures of N9 microglia cells and neuron-glia mixed cultures were exposed to different concentrations of LPS which induced a selective dopaminergic injury. Under these conditions, an increase in microglial reactivity was observed. Additional experiments will be necessary to achieve the main goal of this work. However, these results will support future experiments in order to elucidate the relevance of the anti-inflammatory effect of GDNF on dopaminergic neuroprotection.